Uji Efek Antidiabetik Ekstrak Daun Andong (Cordyline fruticosa L. A. Cheval) Mus musculus yang Diinduksi Streptozotosin - Parawansah Parawansah; Sifak Giatna; Muhammad Ilyas Yusuf (Halu Oleo University, 2015)
The plant andong leaf is a medicinal plant that has not been widely used and contains phenolic, flavonoids,tanins and saponins has many benefits, one of which lower blood glucose levels. This study aim to look at the effects of decrease in blood glucose levels in mice that induced by STZs. The method used was experimental research design is RAL with treatment variations leaf extracts 15%, 30% and 45%, glibenclamid as positive control and Na. CMC negative control. The results were analyzed by ANOVA and continued with Duncan. The results showed that there is a very real difference in the treatment given, andong leaf extracts concentrations is themost effective extracts 15% with the average is 17,67 mg/dL on the hour to three.Key words : Leaf andong, antidiabetic, Mus musculus, streptozotocin.